Strengthening Health System Governance For Achieving Universal Health Coverage: A Comparative Study Of Policy Reforms In Southeast Asia - Nur 'Azah; Siti Fatinnah Binti Ab Rahman (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
Achieving Universal Health Coverage (UHC) necessitates not only increased financial investments in health services but also the establishment of strong governance and accountability mechanisms that ensure equity, transparency, and system-wide efficiency. This article offers a comparative analysis of health system governance reforms in three middle-income Southeast Asian countries Indonesia, the Philippines, and Vietnam each of which has undertaken distinct strategies to accelerate UHC implementation. Using a qualitative policy analysis approach, the study examines institutional reforms, decentralization processes, regulatory innovations, and performance-based accountability tools that have shaped national health agendas. The findings indicate that while all three countries have expanded access to healthcare, the outcomes of governance reforms vary significantly based on factors such as political leadership, subnational administrative capacity, and policy coherence. Indonesia’s efforts in strategic purchasing, the Philippines’ enactment of the Universal Health Care Act, and Vietnam’s emphasis on digital governance and financial transparency each offer context-specific insights into effective reform. Nonetheless, ongoing challenges such as local-level disparities, fragmented data systems, and limited stakeholder influence persist. The article concludes that governance should be viewed not as a peripheral concern but as a central pillar of UHC. Its findings are intended to inform both regional and global policy dialogues on building resilient and accountable health systems.